PHYTOCHEMICAL INVESTIGATION, GC-MS PROFILE AND ANTIMICROBIAL ACTIVITY OF A MEDICINAL PLANT RUTA GRAVEOLENS L. FROM ETHIOPIA - Azalework, Henok Gulilat; ., Sahabjada; Jafri, Asif; Arshad, Md; Malik, Tabarak (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study was designed to screen the phytochemicals present in various solvents extracts of Ruta graveolens (Rue) and furthermore to investigate their antimicrobial activity. Methods: The leaves, stems and seeds of Rue were extracted using four different solvents viz. ethanolic, methanolic, chloroform, and aqueous of varying polarity. The phytochemical screening was carried out qualitatively and Gas Chromatography-Mass Spectroscopy (GC-MS) analysis was performed to identify major phytoconstituents present in the methanolic leaf extract. The antimicrobial effect of extracts was evaluated against six microbial strains namely Bacillus subtillis, Escherichia coli, Proteus vulgaris, Candida albicans, Candida tropicalis and Micrococcus luteus with disc diffusion method. Results: Phytochemical analysis revealed the presence of various secondary metabolites such as flavonoids, alkaloids, terpenoids, saponins and carotenoid. The methanolic leaf extract showed the presence of both tannin and phenolic contents in the higher amount, whereas aqueous extract displayed in the least amount. GC-MS analysis of methanolic leaf extract revealed the presence of approximately 26 phytochemical constituents. The antimicrobial assay revealed that B. subtilis showed a high zone of inhibition (20 mm) at 200 mg/ml of methanolic extract. However, E. coli and C. tropicalis did not show any zone of inhibition against each solvent extract. Conclusion: In conclusion, secondary metabolites present in the extracts have biological activities which warrant further to evaluate in vivo pharmacological studies.